Strategies to Minimise Allergic Conditions in Wounded Servicemen Using the Latest Methods and Drugs - Gai, Leonid; Hruzevskyi, Oleksandr; Kahliak, Mariya; Kobylnyk, Snizhana; Tarasov, Yevhen (Futurity Medicine, 2024)
Aims: To improve existing knowledge in aetiology, diagnosis, management and treatment of allergic and respiratory disorders in military personnel. The paper also discussed specific treatments, best practices, and key sources and advances in the physical environment for optimal health improvement. Study design: A comprehensive review of literature spanning from 2019 to 2024. Methodology: A comprehensive review on minimising allergic conditions in wounded servicemen utilised PubMed to search for relevant literature 2019-2024. Following screening, six studies were chosen from 321 records. Results: The findings summarised in this paper presented valuable information on allergy and general health among soldiers. The research included works with large samples, one of which included over 20 million members of the active military and veterans. Major risks were demonstrated with environmental factors; 77% of participants experienced a contact dermatitis to adhesive tapes, and 61% to colophonium. Accident risks were also highlighted, especially for factors such as fine particulate matter and dust storms. Measures for treating the conditions involved both pharmacological and non-pharmacological methods with individual evaluations and tests like pulmonary function tests and chest CT scans. All these figures implied the need of combating health issues in an effective way within the framework of military groups. Scientific Novelty: This research contributed to the knowledge about allergic in military personnel and developed personalised treatment, prevention and early diagnostics on large scale epidemiological data to promote the health and combat readiness of servicemen. Conclusion: The research mainly focused on allergic and respiratory problems that are more common in military personnel; hence the need for accurate allergens identification and complex treatment plans. The use of technology and the application of individual approaches are vital for the population management, improvement of its richness, and readiness. Therefore, it is important that Military healthcare systems incorporate sound prevention and management practices correspondingly.